1994
DOI: 10.1039/ft9949000113
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamics of liquid binary (alkanenitrile–alkane) mixtures. Part1.—Experimental excess molar volume at 298.15 K and its interpretation with the Prigogine–Flory–Patterson theory

Abstract: Density measurements have been made by means of a vibrating tube densitometer, at 298.15 K, over the whole composition range for 25 binary liquid mixtures of propanenitrile, butanenitrile, pentanenitrile and hexanenitrile with several different hydrocarbons. Values of the molar excess volume, V E , were derived and the results show a regular pattern of behaviour for each of the four sets of binary system. For a given alkanenitrile, the magnitude of V E increases with the hydrocarbon chain length and also for a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

1995
1995
2010
2010

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 18 publications
1
10
0
Order By: Relevance
“…Mixtures were prepared by weight and the density of both the pure components and their mixtures, throughout the composition range, was deterined in previous work [4][5][6] with a vibrating-tube densitometer.…”
Section: Data Reductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Mixtures were prepared by weight and the density of both the pure components and their mixtures, throughout the composition range, was deterined in previous work [4][5][6] with a vibrating-tube densitometer.…”
Section: Data Reductionmentioning
confidence: 99%
“…All liquid samples used for the experiments were obtained from Aldrich, with a reported purity of > 99.5 %, and are the same as those used in other studies reported by our laboratory [3,6]. No further puritication was attempted other than storing the alkanes over sodium and butanenitrile over a molecular sieve in order to eliminate any possible trace of water.…”
Section: Data Reductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Flory's theory [25][26][27][28][29] and its extended forms [30][31][32][33] have been used extensively to predict excess properties of non-electrolyte systems for different kinds of mixtures, including polar components [3,5,7,19,[34][35][36][37][38][39][40][41][42][43][44][45]. The present work reports the applicability of the Prigogine-Flory-Patterson theory (PFP theory) to predict excess molar volume of binary mixtures of ethers with acetonitrile.…”
Section: Theoretical Analysismentioning
confidence: 99%
“…The temperature was controlled within ±0.002 K using a Haake A80 bath-circulator and measured with a digital thermometer, Hewlett Packard 2804 A, using a quartz sensor with a precision of ±0.001 K. The readings from this thermometer were compared with those from a calibrated thermometer Hart Scientific, 1529 Chub-E4 model whose accuracy of ±0.005 K is traceable to the US NIST. The details on the calibration of the densimeter together with the experimental procedure have been included in several previous works [21][22][23][24][25]. The reported density results for each saturated liquid phase were obtained from the average period of vibration, which was in turn obtained from at least 20 stable measurements, whose average standard deviation was ±0.0005.…”
Section: Densitymentioning
confidence: 99%